DISTRIBUTION ANALYSIS OF AVES SPECIES FOR BIODIVERSITY MEASUREMENT IN FOREST AREAS UNAND PADANG (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2014)
Aves species is very abundant in the forest area of Indonesia and its biodiversity is influenced by a number of environmental quality parameters. This research aimed to determine the level of species diversity and abundance of aves species in forest areas of Padang, West Sumatra, Indonesia. The second purpose of this study was to determine factors affecting of diversity and abundance of aves species. The method of this research used bird survey technique (method list of 20 species of birds). This method can be used to complete the list of bird species was found in the forest area, using the quantity of bird species that have been observed. To restrict it, we can use 20 species of aves. Based on this study, in the forest area of UNAND have 21 species of aves. Based on the relative abundance of bird species, the birds most commonly found are species of wallet. Whereas some other aves species have a relative abundance slightly. This happens because of disruption of habitat for aves and forests area by human activities.Keywords : distribution, aves species, measuring of biodiversity